The oxygen reduction reaction catalyzed by Synechocystis sp. PCC 6803 flavodiiron proteins. Issue 11 (19th September 2019) - Brown, Katherine A.; Guo, Zhanjun; Tokmina-Lukaszewska, Monika; Scott, Liam W.; Lubner, Carolyn E.; Smolinski, Sharon; Mulder, David W.; Bothner, Brian; King, Paul W.
Abstract : Photosynthetic flavodiiron proteins catalyze oxygen reduction at non-heme iron sites (brown spheres) using flavin (FMN) mediated electron transfer (black arrows). Abstract : Photosynthetic flavodiiron (Flv) proteins bind flavin and non-heme Fe cofactors and catalyze the oxygen reduction reaction (ORR) coupled to oxidation of reduced pyridine nucleotides during photosynthetic growth. The activity of Flvs have also been observed to form an important catalytic redox loop with water oxidation necessary for preserving photosynthetic electron transport function in cyanobacteria. To determine how these functions may be related, we investigated the kinetic properties of Flv1 and Flv3 from Synechocystis sp. PCC 6803. Under an oxygen atmosphere, Flv1 and Flv3 were found to catalyze ORR with either NADH or NADPH as the electron donor. Reaction velocity curves were sigmoidal and Flv binding of NAD(P)H was cooperative. Based on mass spectrometry generated structural models, each Flv assembles as a homodimer with two oxidoreductase domains capable of binding two molecules of NAD(P)H per subunit, and the flavins are arranged to support electron transfer to the diiron sites for oxygen reduction. Titrations with NAD(P)H resulted in reduction of the diiron site without the accumulation of stable, reduced flavin intermediates. Altogether, the results provide new insights on the properties of Flv1 and Flv3 that enable tight control of reactivity for the complete reduction of oxygen to water, and in this capacity help preserve photosynthetic electron transport function.